Essays in dynamic pricing, channel control and channel competition - Song, Boqian (2016)
Dynamic pricing has been successfully applied in the travel, hospitality, retail and entertainment industries to boost revenue and profits. In recent years, the popularity of the Internet and advances in information technology allow sellers to integrate dynamic pricing into their service bundling/unbundling strategy as well as multi-channel distribution strategy. In this dissertation, we model and analyze several dynamic pricing issues with service unbundling and multiple distribution channels. First, we study the service unbundling issue of a seller who separates the sales of a fixed-priced add-on and dynamically adjusts the price of the capacitated basic service along the horizon. In each period, an arriving consumer makes sequential choice of the basic service and the add-on, the reservation prices of which jointly follow a bivariate distribution. We characterize the structural properties of the optimal price of the basic service and the value function with respect to inventory level, periods-to-go and degree of dependence between the reservation prices. Through an extensive numerical study, we compare the performance of the unbundling strategy with that of the bundling strategy where the seller sells the basic service and the add-on as a bundle. We summarize the situations when the unbundling strategy is profitable. Second, we look at the issue of dynamic pricing of a single perishable product on multiple distribution channels over a fixed horizon. We use stylized linear functions to capture the demand rates of dependent channels, where a proportional or fixed commission might be charged for per unit sold. In response to stochastic demand, the seller dynamically adjusts the control (i.e., openness or closeness) of each distribution channel by changing its product prices on all channels. We derive the optimal channel control policy and establish the one-to-one correspondence between the opportunity cost of capacity and the optimal channel control at any given state, from which the optimal prices can be readily solved. For a distribution system with multiple independent channels or two dependent channels, we characterize the structural properties of the optimal channel control policy. Last, we study a dynamic price competition game between two sellers selling substitutable perishable products over a fixed horizon. We assume that one seller has only one distribution channel while the other seller has one or two distribution channels. Utilizing linear demand rate functions, we formulate each seller’s best response value function as a stochastic dynamic program and prove the existence of a sub-game perfect Nash equilibrium. In particular, we show the existence of a unique sub-game perfect normalized Nash equilibrium where both sellers share identical shadow prices on the constrained strategy space. We find that, at any given state, the normalized Nash equilibrium is uniquely determined by the reservation costs of distribution channels. A distribution channel’s reservation cost is the weighted average of the own and cross opportunity costs of capacity for the seller distributing on the channel. In the numerical study, we examine the impact of the addition of a second distribution channel for the dual-channel seller on the performance of the system.